Assortative Matching on Income - Chiappori, Pierre-André; Fiorio, Carlo; Galichon, Alfred; Verzillo, Stefano (Econometrica, 2026)
We analyze marital matching on income using an extremely rich Dutch data set containing all income tax files over seven years. We develop a novel methodology that directly extends previous contributions to allow for highly flexible matching patterns. Investigating all marriages that took place between 2013 and 2019, we find that marital patterns are particularly intriguing. While a majority of couples match assortatively, a small but significant minority display negative assortative matching. We also show that standard approaches, which consider all married couples using current incomes (as opposed to pre‐marriage incomes used in our approach), may generate misleading conclusions.